Mobilizing sustainable development goals, SDGS through flagship project - the experience of International Islamic University Malaysia - Zen, Irina Safitri (United Nation Country Team in Malaysia, 2019)
Having sustainable development goals, SDGs as a wide spectrum of the normative and integrative framework which voluntarily adopted by the Nation requires active actor involvement to interpret the goals, targets, indicators into action. This is including the higher education institution, HEI as a non-state actor, NSAs. HEI also has recognized as a key driver for SDGs through the Higher Education Sustainability Initiative (HESI). It is a partnership between United Nations Department of Economic and Social Affairs, UNESCO, United Nations Environment, UN Global Compact's Principles for Responsible Management Education (PRME) initiative, United Nations University (UNU), UN-HABITAT and UNCTAD, which was created in 2012 in the run-up to the United Nations Conference on Sustainable Development (Rio+20). Through its strong association with the United Nations, HESI provides higher education institutions with a unique interface between higher education, science, and policymaking. Other HEI network on sustainability is SDSN, UIGreenMetric, green world university ranking, International Sustainable Campus Network (ISCN), South East Asia Sustainable Community Engagement Network (SEASCEN). The five dimensions of SDG; People, Planet, Peace, Prosperity & Partnership is the key drivers to mobilize the SDGs into action. The mechanism to mobilize SDGs in HEI refer to their role and functions as a teaching-learning institution, research development, campus operation sustainably and outreach community. Hence, the partnership or collaboration mode, Triple Helix, Quadruple Helix, and Quintuple Helix was referred. The initial mode of collaboration in the 1990s, the Triple Helix innovation model focuses on the triangulation of university-industry-government relations. The University produces the output or product where the industry produces it for commercialization and the government regulates the market. Second, the Quadruple Helix innovation model where the fourth component, the citizen is taking part in the triple helix interaction. By considering the society, the output needs to be relevant in the context of society. Hence, culture (cultures) and innovation culture (innovation cultures); the knowledge of culture and the culture of knowledge; local knowledge, local value system, values and lifestyles; multiculturalism, multi-culture, and creativity; media; arts and arts universities are considered. Hence, there is a transition from a knowledge-based economy into a knowledge-based society. Finally, the consideration of the natural environment as the fifth knowledge sub-system or helices was considered in the quintuple helix of innovation. It is where the natural environment becomes a consideration. This is triggered by major global environmental challenges, such as climate change, loss of biodiversity, plastic pollution. This situation creates a push factor for the university involves in SDGs. The situation also affects the evolution of the University Mode of Knowledge transfer. From Mode 1 of knowledge as a "Laissez-faire mode" meaning that the education and knowledge are free, transform into Mode 2, where University focuses on knowledge application and a knowledge-based problem solving that involves the following principles: knowledge produced in the context of the application, transdisciplinary. Now, the Mode 3 knowledge production system, expanding and extending the Mode 1 and Mode 2 knowledge production systems are at the heart of the fractal research, education and innovation ecosystem academia together with community and private sector hand in hand in facilitate the state/ government to work on the goals allows more interactions between actors to accommodate sustainability transformation in society. Concurrently, University mission has changed from the First mission to produce skill graduate/labor, into Second mission for knowledge development science and research, and now enter the Third mission for co-creation for sustainability which allows interactions among actors in the Quadruple helix in the bigger context of natural subsystem or quintuple helix (Slide 5). Under the University Third mission, co-creation for sustainability, there are several kinds of research and social engagement paradigms to integrate sustainable development values in society. For example, Participatory and Action research (as a collaborative problem defining, fusion of researcher and subjects, empowerment of reflective social change), Technology Transfer (commercialization of research results, societal contribution through economic development), Transdisciplinary (joint problem solving of real-world problems with multiple actors from society and academia, practice-oriented approach), Cooperative Extension System (an outreach and technology transfer portal to drive local community and rural development), Service Learning (application of educational programs to extracurricular activities for tackling real-world problems), Urban Reform (targeted economic revitalization through direction of university financial resources to local community and real-estate redevelopment, living laboratories (engagement of university research and expertise to establish, monitor and evaluate real-life experiments and social interventions. Use of urban environment as an open collaboration arena. Sustainability in IIUM adopts as a whole institution transformation that integrates SDGs into the University's role and functions; teaching and learning, research development and campus operation. By considering the five principles of human existence under Islamic principle, Maqasid al Shariah; Faith, Life, Intellect, Lineage & Wealth and the 21st century of education philosophy which address four learning dimensions; learning to Know, to Do, to Be and to Live Together. All of these frameworks manifest in the strategic approach of the IIUM Flagship Project for Sustainable Development. It aims to recognize the real-world problem in the community, inter- and transdisciplinary research, part of the University teaching and curriculum i.e. final year thesis, mini project, service learning, partnership, etc. for solution-based approach. There are 29 IIUM flagship projects for SD which adopt the four-pronged approach of mobilization SDG; teaching-learning, research development/ action research, campus operation, and community outreach. Each of the flagship research reflects the third mission of University, accommodates the four-pronged approach, having either the Mode 1, 2 or 3 of knowledge transfer in society, deploy the ESD approach and comply a certain degree or contribute in a various way to Maqasid al shariah. For example, the IIUM River of Life project as a community-based project aims to erase the river pollution problem in Sungai Pusu by creating a sense of belonging of the community adjacent, create responsibility to avoid litter behavior through clean up the river activity in the area surrounding. The educational awareness about the multipurpose of river and function is also part of the government agencies' focus, Department of Irrigation Drainage and Department of Environment, DOE. Friend of Sungai Pusu was established to continuously develop the stewardship function among the youngster and Orang Asli in that area. This project in line with the Fourth Principle of Maqāṣid al-Sharī'ah 'Lineage'. It is to maintain our generation by involving the protection and maintenance of our descendants and all the progeny. It is important to develop a healthy society, productive and civilized. The progeny needs to be taking care to maintain the social system in society. The project deploys the education for sustainable development, ESD as an inter- and trans-disciplinary approach, educate the youngsters and society about the river – learning to know-, how to maintain the river by not polluting them and shows the correct way -learning to do.